Collaboration of Perceived Usefulness and Perceived Ease in Improving Performance with Satisfaction as an Intervening Variable - Marantika , Galih; Thamrin, Muhammad; Hermawan, Haris; Qomariah, Nurul; Setyawan, Rai Rake (Ilomata International Journal of Social Science, 2025)
This study aims to examine the effect of perceived usefulness and perceived ease of use of the Personnel Management Information System (SIMPEG) on employee performance with satisfaction as an intervening variable at the Class II A Jember Correctional Institution. This study uses a quantitative approach with an explanatory research method. The population in this study were all employees of the Class II A Jember Prison totaling 83 people. The data collection techniques used were questionnaires, observation, and documentation. The data analysis techniques used were descriptive analysis and Structural Equation Modeling (SEM) using WarpPLS version 7 software. The results showed that perceived usefulness of use affected employee performance. Perceived ease of use affected employee performance. Perceived usefulness of use affected satisfaction. Perceived ease of use affected satisfaction. Satisfaction affected employee performance. Perceived usefulness of use affected employee performance through satisfaction. Perceived